2023
DOI: 10.1186/s13018-023-03918-y
|View full text |Cite
|
Sign up to set email alerts
|

MiR-137 promotes TLR4/NF-κB pathway activity through targeting KDM4A, inhibits osteogenic differentiation of human bone marrow mesenchymal stem cells and aggravates osteoporosis

Abstract: Purpose As the global population ages rapidly, osteoporotic fractures have become an important public health problem. Previous studies have suggested that miR-137 is involved in the regulation of bone formation, but its specific regulatory mechanism remains unclear. In this study, we aimed to explore the expression, role, and regulatory mechanism of miR-137 in the osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSCs). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Also, TLR4 can be activated by LPS and ovariectomized surgery. Mechanistically, overexpressed Zinc finer E-box binding homeobox 1 (ZEB1), down-regulated KDM4A, overexpressed miR-137, overexpression of circ_0134944, and inhibition of miR-630 ( 12 , 38 , 39 ). Rajpar et al.…”
Section: Biological Profile Of Tlr4mentioning
confidence: 99%
See 4 more Smart Citations
“…Also, TLR4 can be activated by LPS and ovariectomized surgery. Mechanistically, overexpressed Zinc finer E-box binding homeobox 1 (ZEB1), down-regulated KDM4A, overexpressed miR-137, overexpression of circ_0134944, and inhibition of miR-630 ( 12 , 38 , 39 ). Rajpar et al.…”
Section: Biological Profile Of Tlr4mentioning
confidence: 99%
“…As shown in Figure 1 with the flow diagram, thirty studies were finally included. Among them, six included studies ( 39 , 41 45 ) provided the clinical data from osteoporosis patients ( Table 1 ), 17 studies ( 12 , 37 , 38 , 40 , 46 58 ) reported the molecular mechanisms underlying the role of TLR4 in osteoporosis ( Table 2 ), and seven studies ( 59 65 ) provided the data of specific treatments-targeted TLR4 for osteoporosis ( Table 3 ). The key information of the 30 eligible studies included the study object, disease modeling method, the status of TLR4, effect on osteoblast or osteoclast, associated genes or pathways, and the main findings of the independent study.…”
Section: Literature Search For Identifying the Eligible Studiesmentioning
confidence: 99%
See 3 more Smart Citations